Academic Performance: Text Anxiety during examinations of Freshmen Engineering students MLRIT, Hyderabad - Reddy, P. Bhaskara; M, Kantha Reddy; R, Praveen Reddy (Transactions on Engineering and Computing Sciences, 2017)
The main aim of this research was to find the relationship between test anxiety and academic performance of students at the under graduate level. A sample of 414 students was randomly selected from five different departments of Freshman Engineering at MLR Institute of Technology in Hyderabad, TS, India. Data was gathered by utilizing the Test Anxiety Inventory (TAI) developed and improved by Spielberger. Pearson correlation, multivariate English and regression analysis was run for data. It was found that a major negative relationship observed between test anxiety scores and students performance scores. Results proved that a cognitive factor contributes more in test anxiety than effective factors.  Therefore, it is examined that test anxiety is one of the key factors that results the students’ underachievement and poor performance but it can be handled by rigorous training of individual students in linked with factors resulting test anxiety.